Socialization of Indonesia–Malaysia Bilateral Policy in The Field of Education: A Study on Sekolah Indonesia Johor Bahru (SIJB) - Ghoni, Khoirul Abror Ad-Dluha; Esteria, Artha Grace (Khidmatuna: Jurnal Pengabdian Masyarakat, 2025)
Sekolah Indonesia Johor Bahru (SIJB) can be said to be one of the overseas schools that supports immigrant children who do not have documents such as birth certificates and other population data. Since its establishment on February 21, 2017, SIJB has consistently taken part in providing educational services to the Indonesian community in Malaysia which refers to the basis of national education. No less important, that Sekolah Indonesia Johor Bahru plays a role in preserving and promoting Indonesian culture in the Malaysian community, such as the introduction of folk songs and also traditional dances from regions in Indonesia through events made by SIJB. Furthermore, in 2015, with the attention of the central ministry, the SIJB building was established and inaugurated directly by the Minister of Education and Culture Anies Baswedan, until now there are 297 people, the majority of whom are Indonesian migrants working in Malaysia. The contribution of Sekolah Indonesia Johor Bahru in the world of national education is very clear, namely trying to provide access to education to Indonesian children in Malaysia. Bilateral socialization activities integrated with Collaborative Research and Institutional Visits are a community service activity, especially Indonesian migrant children who are in Malaysia. These various activities were carried out in the span of May 22, 2023 at the Indonesian School Johor Bahru, Malaysia. This socialization event began with an introduction to the education system used at Sekolah Indonesia Johor Bahru which was also attended by some students at SIJB which aims to build familiarity between researchers and students. Sekolah Indonesia Johor Bahru is the responsibility of the government in providing rights to all children in terms of education. The material was delivered in the form of a presentation using power point delivered directly by Mrs. Yanti Ramdaniah as the curriculum teacher at Sekolah Indonesia Johor Bahru.